PERIODISMO JURÍDICO. EL TRATAMIENTO INFORMATIVO EN PRENSA DEL CASO ‘MARTA DEL CASTILLO’ EN LOS DIARIOS EL PAÍS Y EL MUNDO - Belén PUEBLA MARTÍNEZ,Vanesa LOZANO VIZCARRO (Fonseca, Journal of Communication, 2023)
This paper proposes, through professional routines of legal journalism, a field work about the covering of ’Marta del Castillo’ case made by the two main newspapers: El País and El Mundo. For that, we used as investigation techniques the content analysis complemented with interviews of the journalist who covered the case in the analyzed newspapers.